AB0661 Efficacy of the Use of Low Dosage and Short Term Programmed Released Prednisone in Spondyloarthritis Patients. (10th June 2014) - Bandinelli, F.; Scazzariello, F.; Pimenta da Fonseca, E.; De Luca, R.; Piemonte, G.; Benelli, L.; Guidi, F.; Guiducci, S.; Santiago, M.B.; Matucci Cerinic, M.
Abstract : Background: Low dose glucocorticoid administration during the night is efficacious on early morning arthritis symptoms [1, 2]. Therefore, low dose treatment of prednisone might be administered in the night, during the maximal pick of IL-6 and TNFa, also in Spondyloarthritis (SpA), where steroids are usually not employed. Objectives: To Investigate the clinical efficacy of low dosage of programmed released prednisone (lodotra® 5 mg –Mundipharma Pharmaceuticals-) assumed at 10 p.m, in SpA patients, evaluated with a three months follow up. Methods: 50 SpA patients (19 male and 31 female, mean 55 [14 standard deviation (SD) and 27-86 interval of confidence (CI)], duration of disease mean 5, 8 [7, 7 SD and 1-48 CI]), all naive from previous glucocorticoids treatment (and out of 15/50 [30%] not treated with DMARDs), were treated for three months with lodotra® 5 mg administration. The results of questionnaires of BASDAI (0-10), fatigue NRS (0-10), axial pain NRS (0-10), peripheral pain NRS (0-10), morning stiffness NRS (0-10) and stiffness duration (minutes) were compared between basal (T0) and after three months therapy (T1) values with Mann Whitney non parametric test. Results: After three months, the difference between activity clinical indices were all significant: BASDAI (mean T0 5, 6/10 vs T1 3, 2/10 p<0, 0001) (figure 1 ), fatigue NRS (mean T0 6, 3/10 vs T1 3, 7/10 p<0, 005), axial pain NRS (mean T0 5, 2/10 vs T1 3, 4/10 p<0, 05), peripheral pain (mean NRS 6, 3/10 vs T1 4, 2/10 p<0, 0005), stiffness NRS (mean T0 6, 5/10 vs T1 3, 8/10 p<0, 0005) and stiffness duration (mean T0 54, 1 vs T1 14, 6 minutes, p<0, 0001). Conclusions: In naive SpA patients, low dose treatment with programmed timing morning release prednisone, may significantly reduce disease activity and reduce either stiffness or pain. References: Arvidson N et al. The timing of glucocorticoid administration in rheumatoid arthritis. Annals Rheum Dis 1997;56:27–31 Cutolo M et al Efficacy of the switch to modified-release prednisone in rheumatoid arthritis patients treated with standard glucocorticoids. Clin Exp Rheumatol 2013; 31: 498-505 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1728